2003
DOI: 10.1159/000074086
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalectomy: Defining Its Role in the Surgical Treatment of Renal Cell Carcinoma

Abstract: Objectives: With the recent widespread use of modern imaging techniques, the frequency of small low-stage renal cell carcinomas (RCC) has grown considerably, giving rise to more conservative surgical approaches. We evaluated the characteristics of adrenal involvement and the accuracy of computerized tomography (CT) in the diagnosis of RCC, defining the real need for adrenalectomy during surgical treatment. Methods: The medical records of 201 patients undergoing radical nephrectomy and ipsilateral adrenalectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
8
0
5
Order By: Relevance
“…As such, the PPV of imaging in our cohort was 33.3% and specificity was calculated at 90.1%. Although a handful of investigators have reported more impressive PPV’s 8, 20 , our data are consistent with reports from other centers in patients with smaller tumors 3, 13, 17, 25, 27, 28 and demonstrate the rigor with which we looked for any radiographic adrenal abnormality. 62.5% (5 of 8) false positive results in our cohort were due to radiographic suspicion of direct tumor invasion into the adrenal rather than an adrenal mass.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…As such, the PPV of imaging in our cohort was 33.3% and specificity was calculated at 90.1%. Although a handful of investigators have reported more impressive PPV’s 8, 20 , our data are consistent with reports from other centers in patients with smaller tumors 3, 13, 17, 25, 27, 28 and demonstrate the rigor with which we looked for any radiographic adrenal abnormality. 62.5% (5 of 8) false positive results in our cohort were due to radiographic suspicion of direct tumor invasion into the adrenal rather than an adrenal mass.…”
Section: Discussionsupporting
confidence: 92%
“…Such low incidence of adrenal involvement in our cohort of large tumors is consistent with the rates of ~1% to ~5% reported in series that include renal masses of all sizes. 4, 8, 1318 Indeed, conflicting data exist regarding whether size alone – independent of the tumor’s ability to invade perinephric tissues or renal vein – is a predictor of adrenal involvement by RCC. 4, 19, 20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La afectación de la glándula ipsilateral habitualmente se relaciona con la proximidad al riñón así como por la existencia de un drenaje venoso y linfático común, principalmente en el lado izquierdo 21 . La incidencia de afectación suprarrenal en el cáncer renal oscila entre el 1,2 y el 10% en las series quirúrgicas 20,[22][23][24][25][26][27] . Este porcentaje se incrementa en las series autopsias de pacientes con enfermedad diseminada, situándose entre el 7 y el 23 % 22,28 .…”
Section: Incidenciaunclassified